2010
DOI: 10.1111/j.1439-0272.2009.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Aurora kinase gene expression in human testicular germ cell tumours

Abstract: The Aurora kinases regulate chromosome segregation and cytokinesis, and alterations in their expression associate with cell malignant transformation. In this study, we demonstrated by qRT-PCR analysis of 14 seminomas that Aurora-A mRNA was, with respect to control tissues, augmented in five of 14 tumour tissues by 2.17 +/- 0.30 fold (P < 0.05) and reduced in 9 to 0.38 +/- 0.10 (P < 0.01). Aurora-B mRNA was increased in 11 tumour tissues by 4.33 +/- 0.82 fold (P < 0.01) and reduced in 3 to 0.41 +/- 0.11 fold. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…AURKC can phosphorylate endogenous histone H3 and evidence suggests that AURKB and AURKC are functionally overlapping 16 . Baldini and colleagues reported deregulated expression of all three aurora kinases in testicular germ cell tumor 17 . The downregulation of AURKC found in our study may result in dysregulated mitosis and more aggressive PTC.…”
Section: Discussionmentioning
confidence: 99%
“…AURKC can phosphorylate endogenous histone H3 and evidence suggests that AURKB and AURKC are functionally overlapping 16 . Baldini and colleagues reported deregulated expression of all three aurora kinases in testicular germ cell tumor 17 . The downregulation of AURKC found in our study may result in dysregulated mitosis and more aggressive PTC.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have led to their evaluation as a potential target for anticancer therapy (Harrington et al 2004, Hata et al 2005, Matthew et al 2006, Manfredi et al 2007, Arlot-Bonnemains et al 2008, Mountzios et al 2008. TGCTs are characterized, as other types of solid tumors, by aneuploidy, and show an altered expression pattern of the aurora kinases (Oosterhuis et al 1989, Roelofs et al 2000, Chieffi et al 2004, Korkola et al 2008, Baldini et al 2010. This evidence identified the aurora kinases as new potential molecular targets also for the treatment of TGCT, especially against the most aggressive forms resistant to the conventional cisplatin-based chemotherapy (Nichols et al 1994, Horwich et al 2006, Fenner et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Chieffi et al (2004) demonstrated through immunohistochemistry the expression of Aurora-B in 51% of seminoma cells and its association with the Ki-67 proliferation marker. More recently, we demonstrated, by means of quantitative RT-PCR and western blot analysis, that the expression of all three aurora kinases is deregulated in TGCT (Baldini et al 2010). Moreover, the chromosome region where the Aurora-C gene maps (19q13.43) is among the chromosomal regions that are most frequently lost in TGCT (Korkola et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important thing in these cells is an altered expression of the aurora kinases family [20], [21], recently observed, associated with malignant cell transformation and genomic instability, [22]. In these studies the aurora Kinase inhibitors were identified and investigated for their capability to reduce “in vitro” NT2 growth and tumorigenicity in order to find a new potential application in cancer therapies [22], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%